How University of Campinas is Coping with Continuous Improvement of Management of Hazardous Waste - Micaroni, Regina Clelia da Costa Mesquita; de Almeida, Amanda Roberta; da Silva, Washington Roberto Rodrigues (Universitas Diponegoro, 2024)
This paper presents the approach that is being used to involve the community not only in handling the hazardous waste in accordance with the policy of the university but also in taking steps forward trying to improve the waste management practices and reduce the amount of waste generated by the campus operation. The approach involves the creation of a group of representatives of the Waste Management Group at each department who are responsible for disseminating the policy and best practices of waste management in their workspace. These representatives are trained to update or create the Local Waste Management Plans (LWMP) of the areas and as a result, currently, 52 areas of University of Campinas have their PGRL updated.